Application of The Two Stay Two Stray Model in Improving Students' Learning Outcomes in Islamic Learning at SMP Negeri 3 Kualuh Selatan - Jamilah; Sugiasti (MANDAILING GLOBAL EDUKASIA, 2024)
Based on the results of initial observations at SMP Negeri 3 Kualuh Selatan in class VIII-4, it shows that the learning process is still less effective. There is no two-way interaction between teachers and students. Likewise, the media used in learning are only blackboards and books. One effort that can be used to improve student activity and learning outcomes is through the use of interesting learning models, one of which is the two stay two stray model. The objectives of this study are: (1) To determine the activity of teachers in using the two stay two stray model in the learning process of Islamic Religious Education for class VIII-4 students on the material of Faith in the Prophet and Messenger of Allah at SMP Negeri 3 Kualuh Selatan. (2) To determine the learning outcomes of class VIII-4 students on the material of Faith in the Prophet and Messenger of Allah at SMP Negeri 3 Kualuh Selatan after the learning process. The method used in this study is Classroom Action Research. The subjects of this study were class VIII-4 students of SMP Negeri 3 Kualuh Selatan. The data collection procedure was through observation of teacher, student and test activities. Data analysis techniques, using the percentage of predetermined success criteria. Based on the research results, it can be concluded that: (1) In cycle I, the percentage value of teacher activity was 80.35%, in cycle II it increased to 89.28% (2). Student learning outcomes in cycle I, the percentage value obtained was 60% and in cycle II it increased to 80 students who had completed individually and classically. Thus, it can be concluded that the implementation of the two stay two stray learning model can improve student learning outcomes on the material of Faith in the Prophet and Messenger of Allah in class VIII-4 of SMP Negeri 3 Kualuh Selatan.